1997
DOI: 10.1007/bf02436889
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modification of silica gels

Abstract: Abstract. Highly porous pure and polyethyleneglycol (PEG)-doped silica gels have been prepared from tetraethyl orthosilicate (TEOS) in ethanol using NH4OH base-catalysis. Addition of PEG to the SiO2-system increases the average particle size and most frequent pore diameter of the resultant gels while their total surface area decreases. The viscosity of the sol increases with PEG concentration and passes through a maximum with increasing molecular weight at PEG 200. Results obtained indicate a definite interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 12 publications
6
40
0
1
Order By: Relevance
“…1 and 2 show the FT-IR and FT-Raman spectra, respectively, of the SiO 2 -PEG (a) sono gels, S1 and (b) classic gels, Cl with different concentration of PEG (MW = 400 g/mole), marked under parenthesis. The spectra of the pure SiO 2 and pure PEG (data not in the same scale) are also shown for direct comparison and found similar to earlier reported data [13][14][15][16][17][18][19][20][21][22][23], The spectra of classic gels was also found similar to that reported earlier for the identical system [6]. The assignment of important bands of SiO 2 -PEG along with its constituents, SiO 2 and PEG are listed in Table 2.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…1 and 2 show the FT-IR and FT-Raman spectra, respectively, of the SiO 2 -PEG (a) sono gels, S1 and (b) classic gels, Cl with different concentration of PEG (MW = 400 g/mole), marked under parenthesis. The spectra of the pure SiO 2 and pure PEG (data not in the same scale) are also shown for direct comparison and found similar to earlier reported data [13][14][15][16][17][18][19][20][21][22][23], The spectra of classic gels was also found similar to that reported earlier for the identical system [6]. The assignment of important bands of SiO 2 -PEG along with its constituents, SiO 2 and PEG are listed in Table 2.…”
Section: Resultssupporting
confidence: 84%
“…Thus, for the pure SiO 2 xerogel having pH < 2.5 (where the silica particles are positively charged), a large number of small sol particles with a large concentration of surface sites for polycondensation results in silica network with large surface area and ink bottle shaped small pores. The addition of PEG into the system hinders the hydrolysis-condensation reactions of monomers, dimers or trimers, which affects the nucleation rate of primary SiO 2 particles leading to agglomeration of a sol containing a much smaller number of particles and thereby produces a network with large pores [6,37], This favors the formation of thermodynamically more stable six-membered siloxane units and induces steric restrictions to form six-membered siloxane rings [26]. However, the silica network well accommodates the 5-10 wt% of PEG in quasi-interpenetrating way without volume expansion resulting in a network with the smallest pores.…”
Section: Siloxane (Si-o-si) Ring Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Each FS particle (average size ¼ 200 nm) was composed of an agglomerate of primary particles with a hydroxyl-rich surface [22,23]. As FS was introduced prior to the base-catalyzed condensation of multi-arm PEG and TEOS [10], binding of the FS to the gel particles introduced a large number of free hydroxyl groups to the matrix, and thus increased hydrogen-bonding interactions between the particles [22,23]. These led to a higher liquefaction stress of the final product .…”
Section: Effect Of Fs On Gel Propertiesmentioning
confidence: 99%
“…Their stability has recently led to conclusions that the forces holding together the two subphases should not be so weak as it has been so far accepted. Thus recent works talk of strong bonds between the two subphases [29,30]. It has even been suggested that covalent bonds can be formed between the two subphases during the solgel process [30].…”
Section: Resultsmentioning
confidence: 99%